2018
DOI: 10.1016/j.ebiom.2018.04.012
|View full text |Cite|
|
Sign up to set email alerts
|

Replication of a Gene-Diet Interaction at CD36, NOS3 and PPARG in Response to Omega-3 Fatty Acid Supplements on Blood Lipids: A Double-Blind Randomized Controlled Trial

Abstract: BackgroundModulation of genetic variants on the effect of omega-3 fatty acid supplements on blood lipids is still unclear.MethodsIn a double-blind randomized controlled trial, 150 patients with type 2 diabetes (T2D) were randomized into omega-3 fatty acid group (n = 56 for fish oil and 44 for flaxseed oil) and control group (n = 50) for 180 days. All patients were genotyped for genetic variants at CD36 (rs1527483), NOS3 (rs1799983) and PPARG (rs1801282). Linear regression was used to examine the interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Genetic variants at PPARG associated with T2DM were only found in GWAS of Europeans but not in East Asians [35]. The effects of n-3 PUFA on blood lipids in type 2 diabetic patients may vary according to the genetic variations of CD36, NOS3 and PPAR-gamma genes, and personalized dietary recommendations based on certain genetic components to improve blood lipid profile may be extremely effective for n-3 PUFA intake [36].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants at PPARG associated with T2DM were only found in GWAS of Europeans but not in East Asians [35]. The effects of n-3 PUFA on blood lipids in type 2 diabetic patients may vary according to the genetic variations of CD36, NOS3 and PPAR-gamma genes, and personalized dietary recommendations based on certain genetic components to improve blood lipid profile may be extremely effective for n-3 PUFA intake [36].…”
Section: Discussionmentioning
confidence: 99%
“…Again, these studies assessed relationships between a number of different genetic variants and study outcomes. In more recent years, several studies (n=8) used a nutri-GRS or polygenic approaches2 60–66 given the plausibility that many gene-lipid/lipoprotein/apolipoprotein and omega-3 interactions are polygenic in nature. Numerous studies assessed genetic variations in the FADS gene cluster,60 61 67–69 APOE, 60 69–78 CD36, 65 79 80 PPARγ2 (62,67,83–85 ) and PPARα 81–83.…”
Section: Resultsmentioning
confidence: 99%
“…In more recent years, several studies (n=8) used a nutri-GRS or polygenic approaches2 60–66 given the plausibility that many gene-lipid/lipoprotein/apolipoprotein and omega-3 interactions are polygenic in nature. Numerous studies assessed genetic variations in the FADS gene cluster,60 61 67–69 APOE, 60 69–78 CD36, 65 79 80 PPARγ2 (62,67,83–85 ) and PPARα 81–83. Among these studies, results related to significant gene–diet (omega-3) associations influencing lipid/lipoprotein outcomes were generally inconsistent except for APOE (rs429358 and rs7412), omega-3 and TG in males only,69–73 75–78 and for a 31-SNP nutri-GRS, omega-3 and TG 63 64.…”
Section: Resultsmentioning
confidence: 99%
“…CD36 is a transmembrane protein expressed in various types of cells, including adipocytes, monocytes, macrophages, platelets, endothelial, and muscle cells [23,24]. This protein belongs to the scavenger receptor [23,25] and binds to lipoproteins, apoptotic cells, and long-chain fatty acids; thus, CD36 is also known as fatty acid translocase [23,26]. Coburn et al demonstrated that long chain fatty acid uptake and utilization have been defective in CD36 knockout mice [27].…”
Section: Descriptive Statisticsmentioning
confidence: 99%